WOMEN’S PARTICIPATIONINPOLITICAL DECISION-MAKING: A COMPARATIVE ANALYSE (MONGOLIAN AND KOREAN CASES) - Б.Одгэрэл (Politology, 2023)
In this paper, the author proposes to study and compare women’s participation in political decision-making of Mongolian and Korean cases. Firstly based on cases examine womenrepresentatives in political decision-making and proposed to study election system outcomes. Secondly study role of Political parties, NGO’s on increasing women’s politicalparticipation.